1. The problem statement, all variables and given/known data - 1/[cosx(cos(x-90))] 3. The attempt at a solution = - 1/[cosx(-cos(90-x))] //so first I take the negative sign out from (x-90) to make it (90-x) = +1/[cosx(cos(90-x))] // negative sign from outside the cos and outside the entire fraction combine to become positive = 1/[cosx(sinx)] //because cos(x-90) = sinx However this answer is incorrect the answer in the back states the following: = -1/[cosx(sinx)] //essentially the same except a negative sign infront of the fraction instead of positive. Why is that though? Can someone please help?